Preparation process of coating for improving corrosion resistance of pressure gauge in special working environment

Through the comprehensive coating preparation process, the problem of corrosion in the pressure gauge case in the chemical environment is solved, and the effect of significantly improving corrosion resistance is achieved, extending the service life and improving product quality.

CN119529626APending Publication Date: 2025-02-28ANHUI MAYI TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411613107.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The pressure gauge case is easily corroded by chemical raw materials in the chemical environment, resulting in insufficient corrosion resistance and affecting service life.

Method used

A comprehensive process, including cold plasma treatment, flame treatment, heating ionization treatment, dispersion treatment and photochemical treatment, is used to prepare a high-performance coating. This process improves the hydrophilicity and adhesion of the resin through a variety of physical and chemical reactions and enhances its corrosion resistance.

Benefits of technology

It significantly improves the chemical corrosion resistance of the pressure gauge case, such as acid resistance, alkali resistance, salt resistance, etc., thereby extending the service life and improving product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation process of a coating for improving corrosion resistance of a pressure gauge in a special working environment, which belongs to the technical field of surface treatment and comprises the following steps: (1) cold plasma treatment; (2) flame treatment; (3) heating ionization treatment; (4) dispersion treatment; and (5) photochemical treatment. According to the preparation technology of the coating for improving the corrosion resistance of the pressure gauge in the special working environment, raw material matching is reasonable, the method is scientific, cold plasma treatment, flame treatment, ionization treatment and the like are combined, and the finally prepared coating is used for a pressure gauge shell; chemical corrosion resistance such as acid resistance, alkali resistance and salt resistance of the pressure gauge shell can be effectively improved, so that the quality of the pressure gauge shell is remarkably improved, and the service life of the pressure gauge shell is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface treatment, and in particular to a preparation process of a coating for improving the corrosion resistance of a pressure gauge under special working conditions. Background Art

[0002] The pressure gauge senses pressure changes through the elastic deformation of the sensitive elements (such as Bourdon tubes, diaphragm boxes, bellows) in the gauge. When the pressure of the measured medium acts on the sensitive element, the sensitive element will undergo elastic deformation, and then the deformation will be transmitted to the pointer through the conversion mechanism of the movement in the gauge, causing the pointer to rotate, thereby indicating the measured pressure value on the dial.

[0003] Since the working environment of the pressure gauge shell is mostly in the chemical field, it is very easy to be corroded by chemical raw materials. Therefore, it is urgent to research and develop a coating for improving the corrosion resistance of the pressure gauge shell to improve the corrosion resistance of the pressure gauge shell. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation process of a coating for improving the corrosion resistance of a pressure gauge under special working environment, so as to solve the deficiencies in the prior art.

[0005] The technical solution adopted by the present invention is as follows: A preparation process of a coating for improving the corrosion resistance of a pressure gauge under a special working environment comprises the following steps: (1) Cold plasma treatment: The natural resin and the epoxy resin are mixed in a weight ratio of 1:6-10 and placed in an air DBD cold plasma treatment device, and the device is started for cold plasma treatment. After completion, the mixture A is taken out for use; (2) Flame treatment: The filler and the mixture A obtained in step (1) are mixed at a weight ratio of 1:34-40 and then placed on the outer flame for flame treatment, and after the mixture is completed, a mixture B is obtained for use; (3) Heating ionization treatment: The mixture B obtained in step (2) is immersed in the treatment liquid, and then the treatment liquid immersed in the mixture B is poured into the electrolytic cell, and the power is turned on to perform heating and ionization treatment. After completion, the mixture is filtered and dried to obtain the mixture C for use; (4) Decentralized processing: Weigh corresponding weight portions of 90-100 parts of the mixture C obtained in step (3), 0.9-1.5 parts of polydimethylsiloxane, 2-2.6 parts of zinc stearate, 4-5 parts of chitosan, 3-5 parts of castor oil, 0.6-0.9 parts of polyether polyester modified organosiloxane, 3-4 parts of silicone oil, and 30-50 parts of water, place them together in a dispersion tank, and disperse them uniformly at a speed of 600-1000 rpm to obtain a dispersion for later use; (5) Photochemical treatment: The dispersion obtained in step (4) is placed in an ultraviolet environment for ultraviolet light irradiation treatment, and then placed in a stirring tank for ultrasonic degassing treatment.

[0006] Furthermore, the power of the cold plasma treatment in step (1) is 2-5 kW, and the number of treatments is 7-9 times.

[0007] By adopting the above technical scheme, the natural resin and the epoxy resin are mixed in a suitable proportion and then placed in a cold plasma treatment device. Under the action of the cold plasma, a variety of physical and chemical reactions occur on the surfaces of the natural resin and the epoxy resin, and etching and roughening occur. Certain oxygen-containing polar groups can also be introduced to improve the hydrophilicity and adhesion of the resin, promote the fusion between the natural resin and the epoxy resin, and partially weaken or even completely weaken the interface effect between the resin and the filler.

[0008] Furthermore, the filler in step (2) is at least one of diatomaceous earth, graphene, attapulgite, and nano zinc oxide.

[0009] Furthermore, during the flame treatment in step (2), the horizontal distance between the mixture A and the outer flame of the flame is controlled to be 0.4-1 cm, and the treatment time is 12-18 min.

[0010] By adopting the above technical solution, the obtained mixed resin and filler are mixed evenly and then placed on the outer flame for flame treatment. Through the gas flame, the flame contains O, NO, OH and NH free radicals in an excited state, which are then oxidized on the surface according to the free radical mechanism, and some polar oxygen-containing groups are introduced to cause chain breaking reaction. Thus, the adhesion between the filler and the coating matrix components is improved.

[0011] Furthermore, the components and corresponding weight percentages in the treatment solution described in step (3) are: 2-3% ammonium chloride, 5-7% ammonia water, 1-2% diammonium dihydrogen phosphate, 0.9-1.3% triethyl chloride or tributyltin, and the balance is pure water.

[0012] Furthermore, during the heating ionization treatment in step (3), the temperature in the treatment liquid is controlled to be 70-80° C., the voltage is 180-220 V, the current is 6-10 A, and the treatment time is 19-25 min.

[0013] By adopting the above technical scheme, the obtained mixture is immersed in a treatment liquid, the power is turned on, the voltage, current and temperature are controlled, and some components in the treatment liquid will be partially ionized to form cations and anions, which act on the surface of the mixture to reduce the degree of polymerization of the mixture, thereby laying a good foundation for subsequent homogeneous dispersion. In addition, when the degree of polymerization is reduced, the mixture quickly absorbs the effective ingredients in the treatment liquid under high temperature conditions, and the anti-mildew and antibacterial components therein are fully absorbed by the mixture, effectively enhancing the corrosion resistance of the mixture.

[0014] Furthermore, during the ultraviolet light irradiation treatment in step (5), the wavelength of the ultraviolet light is controlled to be 200-400 nm, and the treatment time is 1-2 hours.

[0015] Furthermore, during the ultrasonic degassing treatment in step (5), the frequency of the ultrasonic wave is controlled to be 45-65 kHz, and the time of the ultrasonic degassing treatment is 30-40 min.

[0016] By adopting the above technical scheme, the obtained mixture is evenly dispersed with dispersants, defoamers, leveling agents, etc. and then photochemically treated. Ultraviolet light irradiation causes the polymer surface to crack, crosslink and oxidize, thereby improving the surface wettability. During ultrasonic degassing, the dispersion will be further evenly dispersed to form a homogeneous and refined finished product.

[0017] The present invention has the following beneficial effects: The present application provides a preparation process for a coating for improving the corrosion resistance of pressure gauges under special working environments. The raw materials are reasonably matched and the method is scientific. Cold plasma treatment, flame treatment, ionization treatment, etc. are combined. The finally prepared coating is used for the pressure gauge shell, which can effectively improve the acid resistance, alkali resistance, salt resistance and other chemical corrosion resistance of the pressure gauge shell, thereby significantly improving the quality of the pressure gauge shell and extending the service life of the pressure gauge shell. DETAILED DESCRIPTION

[0018] The following will be described clearly and completely in conjunction with the technical solutions of the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0019] A preparation process of a coating for improving the corrosion resistance of a pressure gauge under a special working environment comprises the following steps: (1) Cold plasma treatment: The natural resin and the epoxy resin were mixed in a weight ratio of 1:6 and placed in an air DBD cold plasma treatment device, and the device was started for cold plasma treatment. After completion, the mixture A was taken out for use; (2) Flame treatment: The filler and the mixture A obtained in step (1) are mixed at a weight ratio of 1:34 and then placed on the outer flame for flame treatment. After the mixture is treated, a mixture B is obtained for use; (3) Heating ionization treatment: The mixture B obtained in step (2) is immersed in the treatment liquid, and then the treatment liquid immersed in the mixture B is poured into the electrolytic cell, and the power is turned on to perform heating and ionization treatment. After completion, the mixture is filtered and dried to obtain the mixture C for use; (4) Decentralized processing: Weigh corresponding weight portions of 90 parts of the mixture C obtained in step (3), 0.9 parts of polydimethylsiloxane, 2 parts of zinc stearate, 4 parts of chitosan, 3 parts of castor oil, 0.6 parts of polyether polyester modified organosiloxane, 3 parts of silicone oil, and 30 parts of water, place them together in a dispersion tank, and disperse them uniformly at a speed of 600 rpm to obtain a dispersion for later use; (5) Photochemical treatment: The dispersion obtained in step (4) is placed in an ultraviolet environment for ultraviolet light irradiation treatment, and then placed in a stirring tank for ultrasonic degassing treatment.

[0020] The power of the cold plasma treatment in step (1) is 2 kW, and the number of treatments is 7 times.

[0021] The filler described in step (2) is at least one of diatomaceous earth, graphene, attapulgite, and nano zinc oxide.

[0022] During the flame treatment in step (2), the horizontal distance between the mixture A and the outer flame of the flame is controlled to be 0.4 cm, and the treatment time is 12 minutes.

[0023] The components and corresponding weight percentages in the treatment solution described in step (3) are: 2% ammonium chloride, 5% ammonia water, 1% diammonium phosphate, 0.9% triethyl chloride or tributyltin, and the balance is pure water.

[0024] During the heating ionization treatment in step (3), the temperature in the treatment liquid was controlled to be 70° C., the voltage was 180 V, the current was 6 A, and the treatment time was 19 min.

[0025] During the ultraviolet light irradiation treatment described in step (5), the wavelength of the ultraviolet light is controlled to be 200 nm and the treatment time is 1 hour.

[0026] During the ultrasonic degassing treatment in step (5), the frequency of the ultrasonic wave is controlled to be 45 kHz, and the time of the ultrasonic degassing treatment is 30 minutes. Example 2

[0027] A preparation process of a coating for improving the corrosion resistance of a pressure gauge under a special working environment comprises the following steps: (1) Cold plasma treatment: The natural resin and the epoxy resin were mixed in a weight ratio of 1:8 and placed in an air DBD cold plasma treatment device, and the device was started for cold plasma treatment. After the treatment was completed, the mixture A was taken out for use; (2) Flame treatment: The filler and the mixture A obtained in step (1) are mixed at a weight ratio of 1:37 and then placed on the outer flame for flame treatment, and after the mixture is treated, a mixture B is obtained for use; (3) Heating ionization treatment: The mixture B obtained in step (2) is immersed in the treatment liquid, and then the treatment liquid immersed in the mixture B is poured into the electrolytic cell, and the power is turned on to perform heating and ionization treatment. After completion, the mixture is filtered and dried to obtain the mixture C for use; (4) Decentralized processing: Weigh corresponding weight portions of 95 parts of the mixture C obtained in step (3), 1.2 parts of polydimethylsiloxane, 2.3 parts of zinc stearate, 4.5 parts of chitosan, 4 parts of castor oil, 0.75 parts of polyether polyester modified organosiloxane, 3.5 parts of silicone oil, and 40 parts of water, place them together in a dispersion tank, and disperse them uniformly at a speed of 800 rpm to obtain a dispersion for later use; (5) Photochemical treatment: The dispersion obtained in step (4) is placed in an ultraviolet environment for ultraviolet light irradiation treatment, and then placed in a stirring tank for ultrasonic degassing treatment.

[0028] The power of the cold plasma treatment in step (1) is 3.5 kW, and the number of treatments is 8 times.

[0029] The filler described in step (2) is at least one of diatomaceous earth, graphene, attapulgite, and nano zinc oxide.

[0030] During the flame treatment in step (2), the horizontal distance between the mixture A and the outer flame of the flame is controlled to be 0.7 cm, and the treatment time is 15 minutes.

[0031] The components and corresponding weight percentages in the treatment solution described in step (3) are: 2.5% ammonium chloride, 6% ammonia water, 1.5% diammonium phosphate, 1.1% triethyl chloride or tributyltin, and the balance is pure water.

[0032] During the heating ionization treatment in step (3), the temperature in the treatment liquid is controlled to be 75° C., the voltage is 200 V, the current is 8 A, and the treatment time is 22 min.

[0033] During the ultraviolet light irradiation treatment described in step (5), the wavelength of the ultraviolet light is controlled to be 300 nm and the treatment time is 1.5 h.

[0034] During the ultrasonic degassing treatment in step (5), the frequency of the ultrasonic wave is controlled to be 55 kHz, and the time of the ultrasonic degassing treatment is 35 minutes. Example 3

[0035] A preparation process of a coating for improving the corrosion resistance of a pressure gauge under a special working environment comprises the following steps: (1) Cold plasma treatment: The natural resin and the epoxy resin were mixed in a weight ratio of 1:10 and placed in an air DBD cold plasma treatment device, and the device was started to perform cold plasma treatment. After completion, the mixture A was taken out for use; (2) Flame treatment: The filler and the mixture A obtained in step (1) are mixed at a weight ratio of 1:40 and then placed on the outer flame for flame treatment, and after the mixture is treated, a mixture B is obtained for use; (3) Heating ionization treatment: The mixture B obtained in step (2) is immersed in the treatment liquid, and then the treatment liquid immersed in the mixture B is poured into the electrolytic cell, and the power is turned on to perform heating and ionization treatment. After completion, the mixture is filtered and dried to obtain the mixture C for use; (4) Decentralized processing: Weigh corresponding weight portions of 100 parts of the mixture C obtained in step (3), 1.5 parts of polydimethylsiloxane, 2.6 parts of zinc stearate, 5 parts of chitosan, 5 parts of castor oil, 0.9 parts of polyether polyester modified organosiloxane, 4 parts of silicone oil, and 50 parts of water, place them together in a dispersion tank, and disperse them uniformly at a speed of 1000 rpm to obtain a dispersion for later use; (5) Photochemical treatment: The dispersion obtained in step (4) is placed in an ultraviolet environment for ultraviolet light irradiation treatment, and then placed in a stirring tank for ultrasonic degassing treatment.

[0036] The power of the cold plasma treatment in step (1) is 5 kW and the number of treatments is 9 times.

[0037] The filler described in step (2) is at least one of diatomaceous earth, graphene, attapulgite, and nano zinc oxide.

[0038] During the flame treatment in step (2), the horizontal distance between the mixture A and the outer flame of the flame is controlled to be 1 cm, and the treatment time is 18 minutes.

[0039] The components and corresponding weight percentages in the treatment solution described in step (3) are: 3% ammonium chloride, 7% ammonia water, 2% diammonium phosphate, 1.3% triethyl chloride or tributyltin, and the balance is pure water.

[0040] During the heating ionization treatment in step (3), the temperature in the treatment liquid is controlled to be 80° C., the voltage is 220 V, the current is 10 A, and the treatment time is 25 min.

[0041] During the ultraviolet light irradiation treatment described in step (5), the wavelength of the ultraviolet light is controlled to be 400 nm and the treatment time is 2 hours.

[0042] During the ultrasonic degassing treatment in step (5), the frequency of the ultrasonic wave is controlled to be 65 kHz, and the time of the ultrasonic degassing treatment is 40 minutes.

[0043] Comparative Example 1 A preparation process of a coating for improving the corrosion resistance of a pressure gauge under a special working environment comprises the following steps: (1) Mixed processing: The natural resin and the epoxy resin are mixed in a weight ratio of 1:8 to obtain a mixture A for later use; (2) Flame treatment: The filler and the mixture A obtained in step (1) are mixed at a weight ratio of 1:37 and then placed on the outer flame for flame treatment, and after the mixture is treated, a mixture B is obtained for use; (3) Heating ionization treatment: The mixture B obtained in step (2) is immersed in the treatment liquid, and then the treatment liquid immersed in the mixture B is poured into the electrolytic cell, and the power is turned on to perform heating and ionization treatment. After completion, the mixture is filtered and dried to obtain the mixture C for use; (4) Decentralized processing: Weigh corresponding weight portions of 95 parts of the mixture C obtained in step (3), 1.2 parts of polydimethylsiloxane, 2.3 parts of zinc stearate, 4.5 parts of chitosan, 4 parts of castor oil, 0.75 parts of polyether polyester modified organosiloxane, 3.5 parts of silicone oil, and 40 parts of water, place them together in a dispersion tank, and disperse them uniformly at a speed of 800 rpm to obtain a dispersion for later use; (5) Photochemical treatment: The dispersion obtained in step (4) is placed in an ultraviolet environment for ultraviolet light irradiation treatment, and then placed in a stirring tank for ultrasonic degassing treatment.

[0044] The power of the cold plasma treatment in step (1) is 3.5 kW, and the number of treatments is 8 times.

[0045] The filler described in step (2) is at least one of diatomaceous earth, graphene, attapulgite, and nano zinc oxide.

[0046] During the flame treatment in step (2), the horizontal distance between the mixture A and the outer flame of the flame is controlled to be 0.7 cm, and the treatment time is 15 minutes.

[0047] The components and corresponding weight percentages in the treatment solution described in step (3) are: 2.5% ammonium chloride, 6% ammonia water, 1.5% diammonium phosphate, 1.1% triethyl chloride or tributyltin, and the balance is pure water.

[0048] During the heating ionization treatment in step (3), the temperature in the treatment liquid is controlled to be 75° C., the voltage is 200 V, the current is 8 A, and the treatment time is 22 min.

[0049] During the ultraviolet light irradiation treatment described in step (5), the wavelength of the ultraviolet light is controlled to be 300 nm and the treatment time is 1.5 h.

[0050] During the ultrasonic degassing treatment in step (5), the frequency of the ultrasonic wave is controlled to be 55 kHz, and the time of the ultrasonic degassing treatment is 35 minutes.

[0051] Comparative Example 2 A preparation process of a coating for improving the corrosion resistance of a pressure gauge under a special working environment comprises the following steps: (1) Cold plasma treatment: The natural resin and the epoxy resin were mixed in a weight ratio of 1:8 and placed in an air DBD cold plasma treatment device, and the device was started for cold plasma treatment. After the treatment was completed, the mixture A was taken out for use; (2) Mixing process: The filler and the mixture A obtained in step (1) are mixed at a weight ratio of 1:37 to obtain a mixture B for later use; (3) Heating ionization treatment: The mixture B obtained in step (2) is immersed in the treatment liquid, and then the treatment liquid immersed in the mixture B is poured into the electrolytic cell, and the power is turned on to perform heating and ionization treatment. After completion, the mixture is filtered and dried to obtain the mixture C for use; (4) Decentralized processing: Weigh corresponding weight portions of 95 parts of the mixture C obtained in step (3), 1.2 parts of polydimethylsiloxane, 2.3 parts of zinc stearate, 4.5 parts of chitosan, 4 parts of castor oil, 0.75 parts of polyether polyester modified organosiloxane, 3.5 parts of silicone oil, and 40 parts of water, place them together in a dispersion tank, and disperse them uniformly at a speed of 800 rpm to obtain a dispersion for later use; (5) Photochemical treatment: The dispersion obtained in step (4) is placed in an ultraviolet environment for ultraviolet light irradiation treatment, and then placed in a stirring tank for ultrasonic degassing treatment.

[0052] The power of the cold plasma treatment in step (1) is 3.5 kW, and the number of treatments is 8 times.

[0053] The filler described in step (2) is at least one of diatomaceous earth, graphene, attapulgite, and nano zinc oxide.

[0054] During the flame treatment in step (2), the horizontal distance between the mixture A and the outer flame of the flame is controlled to be 0.7 cm, and the treatment time is 15 minutes.

[0055] The components and corresponding weight percentages in the treatment solution described in step (3) are: 2.5% ammonium chloride, 6% ammonia water, 1.5% diammonium phosphate, 1.1% triethyl chloride or tributyltin, and the balance is pure water.

[0056] During the heating ionization treatment in step (3), the temperature in the treatment liquid is controlled to be 75° C., the voltage is 200 V, the current is 8 A, and the treatment time is 22 min.

[0057] During the ultraviolet light irradiation treatment described in step (5), the wavelength of the ultraviolet light is controlled to be 300 nm and the treatment time is 1.5 h.

[0058] During the ultrasonic degassing treatment in step (5), the frequency of the ultrasonic wave is controlled to be 55 kHz, and the time of the ultrasonic degassing treatment is 35 minutes.

[0059] Comparative Example 3 A preparation process of a coating for improving the corrosion resistance of a pressure gauge under a special working environment comprises the following steps: (1) Cold plasma treatment: The natural resin and the epoxy resin were mixed in a weight ratio of 1:8 and placed in an air DBD cold plasma treatment device, and the device was started for cold plasma treatment. After the treatment was completed, the mixture A was taken out for use; (2) Flame treatment: The filler and the mixture A obtained in step (1) are mixed at a weight ratio of 1:37 and then placed on the outer flame for flame treatment, and after the mixture is treated, a mixture B is obtained for use; (3) Decentralized processing: Weigh corresponding weight portions of 95 parts of the mixture B obtained in step (2), 1.2 parts of polydimethylsiloxane, 2.3 parts of zinc stearate, 4.5 parts of chitosan, 4 parts of castor oil, 0.75 parts of polyether polyester modified organosiloxane, 3.5 parts of silicone oil, and 40 parts of water, place them together in a dispersion tank, and disperse them uniformly at a speed of 800 rpm to obtain a dispersion for later use; (4) Photochemical treatment: The dispersion obtained in step (3) is placed in an ultraviolet environment for ultraviolet light irradiation treatment, and then placed in a stirring tank for ultrasonic degassing treatment.

[0060] The power of the cold plasma treatment in step (1) is 3.5 kW, and the number of treatments is 8 times.

[0061] The filler described in step (2) is at least one of diatomaceous earth, graphene, attapulgite, and nano zinc oxide.

[0062] During the flame treatment in step (2), the horizontal distance between the mixture A and the outer flame of the flame is controlled to be 0.7 cm, and the treatment time is 15 minutes.

[0063] During the ultraviolet light irradiation treatment described in step (4), the wavelength of the ultraviolet light is controlled to be 300 nm and the treatment time is 1.5 h.

[0064] During the ultrasonic degassing treatment in step (4), the frequency of the ultrasonic wave is controlled to be 55 kHz, and the time of the ultrasonic degassing treatment is 35 minutes.

[0065] Comparative Example 4 A preparation process of a coating for improving the corrosion resistance of a pressure gauge under a special working environment comprises the following steps: (1) Cold plasma treatment: The natural resin and the epoxy resin were mixed in a weight ratio of 1:8 and placed in an air DBD cold plasma treatment device, and the device was started for cold plasma treatment. After the treatment was completed, the mixture A was taken out for use; (2) Flame treatment: The filler and the mixture A obtained in step (1) are mixed at a weight ratio of 1:37 and then placed on the outer flame for flame treatment, and after the mixture is treated, a mixture B is obtained for use; (3) Heating ionization treatment: The mixture B obtained in step (2) is immersed in the treatment liquid, and then the treatment liquid immersed in the mixture B is poured into the electrolytic cell, and the power is turned on to perform heating and ionization treatment. After completion, the mixture is filtered and dried to obtain the mixture C for use; (4) Decentralized processing: Weigh corresponding weight portions of 95 parts of the mixture C obtained in step (3), 1.2 parts of polydimethylsiloxane, 2.3 parts of zinc stearate, 4.5 parts of chitosan, 4 parts of castor oil, 0.75 parts of polyether polyester modified organosiloxane, 3.5 parts of silicone oil, and 40 parts of water, place them together in a dispersion tank, and disperse them evenly at a rotation speed of 800 rpm.

[0066] The power of the cold plasma treatment in step (1) is 3.5 kW, and the number of treatments is 8 times.

[0067] The filler described in step (2) is at least one of diatomaceous earth, graphene, attapulgite, and nano zinc oxide.

[0068] During the flame treatment in step (2), the horizontal distance between the mixture A and the outer flame of the flame is controlled to be 0.7 cm, and the treatment time is 15 minutes.

[0069] The components and corresponding weight percentages in the treatment solution described in step (3) are: 2.5% ammonium chloride, 6% ammonia water, 1.5% diammonium phosphate, 1.1% triethyl chloride or tributyltin, and the balance is pure water.

[0070] During the heating ionization treatment in step (3), the temperature in the treatment liquid is controlled to be 75° C., the voltage is 200 V, the current is 8 A, and the treatment time is 22 min.

[0071] Control group: Application number: CN201710833819.X discloses a corrosion-resistant coating.

[0072] In order to compare the technical effects of the present application, the same batch of pressure gauge shells of the same specifications and models were selected as test objects, and the selected pressure gauge shells were randomly divided into 7 groups of equal quality and quantity, of which 6 groups were test groups and 1 group was a blank control group. Then, the coatings were prepared by the methods of Example 2, Comparative Examples 1 to 4 and the control group, respectively. Then, the coatings of Example 2, Comparative Examples 1 to 4 and the control group were applied to the surfaces of the corresponding pressure gauge shells in the same coating manner. After completion, 6 pressure gauge shells were taken from each group (including the blank control group) and immersed in 10moL / L HCl solution, 6 pressure gauge shells were taken and immersed in 10moL / L NaOH solution, and 6 pressure gauge shells were taken and immersed in 10moL / L NaCl solution. The time (h) for corrosion of the pressure gauge shells in each group was observed and recorded and statistically analyzed.

[0073] The specific test comparison data are shown in Table 1 below: Table 1

[0074] It can be seen from Table 1 above that the present application provides a preparation process for a coating that improves the corrosion resistance of pressure gauges under special working environments. The raw materials are reasonably matched and the method is scientific. Cold plasma treatment, flame treatment, ionization treatment, etc. are combined. The finally prepared coating is used for the pressure gauge shell, which can effectively improve the acid resistance, alkali resistance, salt resistance and other chemical corrosion resistance of the pressure gauge shell, thereby significantly improving the quality of the pressure gauge shell and extending the service life of the pressure gauge shell.

[0075] The above description is only a preferred embodiment of the present invention, but the present invention is not limited to the scope of implementation shown. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which still do not exceed the spirit covered by the specification, should be within the protection scope of the present invention.

Claims

1. A preparation process for a coating for improving the corrosion resistance of a pressure gauge under a special working environment, characterized in that: The steps include: (1) Cold plasma treatment: The natural resin and the epoxy resin are mixed in a weight ratio of 1:6-10 and placed in an air DBD cold plasma treatment device, and the device is started for cold plasma treatment. After completion, the mixture A is taken out for use; (2) Flame treatment: The filler and the mixture A obtained in step (1) are mixed at a weight ratio of 1:34-40 and then placed on the outer flame for flame treatment, and after the mixture is completed, a mixture B is obtained for use; (3) Heating ionization treatment: The mixture B obtained in step (2) is immersed in the treatment liquid, and then the treatment liquid immersed in the mixture B is poured into the electrolytic cell, and the power is turned on to perform heating and ionization treatment. After completion, the mixture is filtered and dried to obtain the mixture C for use; (4) Decentralized processing: Weigh corresponding weight portions of 90-100 parts of the mixture C obtained in step (3), 0.9-1.5 parts of polydimethylsiloxane, 2-2.6 parts of zinc stearate, 4-5 parts of chitosan, 3-5 parts of castor oil, 0.6-0.9 parts of polyether polyester modified organosiloxane, 3-4 parts of silicone oil, and 30-50 parts of water, place them together in a dispersion tank, and disperse them uniformly at a speed of 600-1000 rpm to obtain a dispersion for later use; (5) Photochemical treatment: The dispersion obtained in step (4) is placed in an ultraviolet environment for ultraviolet light irradiation treatment, and then placed in a stirring tank for ultrasonic degassing treatment.

2. According to claim 1, a preparation process of a coating for improving the corrosion resistance of a pressure gauge under a special working environment, characterized in that: The power of the cold plasma treatment in step (1) is 2-5 kW, and the number of treatments is 7-9 times.

3. According to claim 1, a preparation process of a coating for improving the corrosion resistance of a pressure gauge under a special working environment, characterized in that: The filler described in step (2) is at least one of diatomaceous earth, graphene, attapulgite, and nano zinc oxide.

4. According to claim 1, a preparation process of a coating for improving the corrosion resistance of a pressure gauge under a special working environment, characterized in that: During the flame treatment in step (2), the horizontal distance between the mixture A and the outer flame of the flame is controlled to be 0.4-1 cm, and the treatment time is 12-18 minutes.

5. According to claim 1, a preparation process of a coating for improving the corrosion resistance of a pressure gauge under a special working environment, characterized in that: The components and corresponding weight percentages in the treatment solution described in step (3) are: 2-3% ammonium chloride, 5-7% ammonia water, 1-2% diammonium dihydrogen phosphate, 0.9-1.3% triethyl chloride or tributyltin, and the balance is pure water.

6. According to claim 1, a preparation process of a coating for improving the corrosion resistance of a pressure gauge under a special working environment, characterized in that: During the heating ionization treatment in step (3), the temperature in the treatment liquid is controlled to be 70-80°C, the voltage is 180-220V, the current is 6-10A, and the treatment time is 19-25min.

7. According to claim 1, a preparation process of a coating for improving the corrosion resistance of a pressure gauge under a special working environment, characterized in that: During the ultraviolet light irradiation treatment described in step (5), the wavelength of the ultraviolet light is controlled to be 200~400nm, and the treatment time is 1~2h.

8. According to claim 1, a preparation process of a coating for improving the corrosion resistance of a pressure gauge under a special working environment, characterized in that: During the ultrasonic degassing treatment in step (5), the frequency of the ultrasonic wave is controlled to be 45-65 kHz, and the time of the ultrasonic degassing treatment is 30-40 minutes.

Citation Information

Patent Citations

  • Corrosion-resistant coating

    CN107699101A